Modifikasi Model Edukasi di Masa Pandemi untuk Menjaga Ketaatan Diet dan Minum Obat Pasien Diabetes Melitus - Joko Sudarsono; Budiyanti Wiboworini; Yulia Lanti Retno Dewi; Dwi Rahayu; Amelya Augusthina Ayusari; Widardo Widardo; Kusmadewi Eka Damayanti; Risalina Myrtha; Sutartinah Sri Handayani; Kisrini Kisrini (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Indonesian Red Cross (PMI) as a partner has a clinic for patients with chronic diseases with regular inspections and education. Diabetes mellitus is one of the most common disease in PMI clinic, with main problems are diet style and medicine compliance. The pandemic has caused the clinic activities stopped; so it is necessary to modify the patients’ educational methods. Limitations in face-to-face education during pandemic, could be overcome by digital-based education. Community service activities were carried out through the identification of partner problems; collecting data on patients or patients' families with WhatsApp numbers, making scripts followed by making videos; distributing the video via Google Drive and Youtube and ended with a discussion session via WhatsApp group. The education contents include menus preparation and managing macronutrient intake and public education in medicine compliance. Changes in knowledge was measured from the results of the pretest and posttest related to the material. The results showed an increase in knowledge of good menu preparation to meet the needs of both macronutrients and micronutrients as well as knowledge of the correct use of diabetes drugs by 20%. These results indicated that the use of video and digital education through WhatsApp group can be an alternative of patients education during pandemic.